Social Engineering SWOT Analysis in Government-Owned Commercial Banks and National Private Commercial Banks - Syafitri, Nadillah; Agustin, Grisvia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
This research examines the phenomenon of social engineering at government-owned commercial banks and national private commercial banks. The research method used is descriptive qualitative with a literature study. The research results show the bank's strengths, weaknesses, opportunities, and threats. In addition, several strategies are recommended for banks to prevent social engineering attacks, namely building information technology in banking according to the standards and regulations of the Financial Service Authority (Otoritas Jasa Keuangan), utilizing social media as an educational tool, training employees, monitoring and optimizing data security and banking information technology networks, suppressing the circulation of social issues on behalf of banks that can trigger social engineering, increasing financial literacy and awareness of data security personal customers and employees. To prevent social engineering attacks, banks can implement strategies that are considered adequate.